Oxidative stress, reduced glutathione levels and catalase activities in leprosy patients - Ozan, G.; Yilmaz, S.; Erisir, M.; Erden, I.; Ozan, S. Temizer (Wiley, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY